Pelvic recurrence of an ovarian seromucinous borderline tumor detected by vaginal cytology: A case report and review of the literature. Issue 11 (6th July 2016) - Hayashi, Hironori; Taniguchi, Shuichi; Kurihara, Shuichi; Hachisuga, Kazuhisa; Fukuda, Saori; Inada, Chifumi; Shimao, Yoshiya; Marutsuka, Kousuke; Shimamoto, Tomihiro
Abstract : Seromucinous borderline tumors are typically confined to the ovaries and rarely relapse after surgery. We report the case of a woman with a seromucinous borderline tumor with peritoneal implant at the Douglas pouch, who was affected by a recurrent tumor at the vaginal stump 2 years and 6 months after the primary surgery. The recurrent lesion was detected by vaginal cytology. Histology of the recurrent lesion showed perineural infiltration, and progression to low‐grade adenocarcinoma was suggested. After the second surgery, vaginal cytology showed that the tumor cells remained positive. At postoperative follow‐ups of ovarian borderline tumors, an examination of the specific region where recurrence is likely to occur can contribute to the early detection of tumor relapse. Diagn. Cytopathol. 2016;44:912–916. © 2016 Wiley Periodicals, Inc.